Pelatihan Tata Kelola Keuangan UMKM Pada Kelurahan Bugangan Semarang - Dian Prasetyo Widyaningtyas; Bonaventura Hendrawan Maranata (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
Effective and efficient financial management is essential for the success of UMKM. However, UMKM are often hampered in optimizing their performance and competitiveness due to lack of knowledge and skills in financial management. Therefore, this community service aims to train UMKM in financial management to improve their financial literacy and their ability to utilize skills in business management. This activity uses a participatory approach by involving UMKM in the Bugangan Village area and the method includes theoretical explanations and direct practical assistance. The training materials include basic concepts of financial management and simple financial report analysis. The results showed that participants had a better understanding and skills to manage business finances more effectively. In addition, participants also reported increased time efficiency and accuracy of financial records after the training was implemented. Thus, this program is expected to help UMKM become more adaptive to the demands of the digital era and contribute to sustainable local economic growth.